Benign infantile seizures associated with mild gastroenteritis: clinical and electroencephalographic characteristics - V. Yu. Nogovitsyn; Yu. Bobylova (Русский журнал детской неврологии, 2019)
Benign infantile seizures associated with mild gastroenteritis are a special type of situationally determined seizures in infants. Usually, clinical manifestations are observed between 4 month and 3 years of age, most commonly during the second year of life. Vomiting and diarrhea are the key symptoms, although their severity may vary. Other typical signs include multiple serial seizures (focal, secondarily generalized) over several days accompanying enteric infection (caused by rotavirus, norovirus, rarely sapoviruses, adenovirus, or Coxsackie virus), no changes in the interictal electroencephalogram, and favorable prognosis. Differential diagnosis should include neuroinfections, fluid and electrolyte disorders, epilepsy, and febrile seizures. Examination should include analysis of blood and cerebrospinal fluid and electroencephalography. The majority of patients have normal interictal electroencephalogram. The authors present own observations.